2009
DOI: 10.3168/jds.2008-1414
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the influence of Saccharomyces cerevisiae supplementation on ruminal parameters and milk production of ruminants

Abstract: The effects of yeast supplementation on intake, production, and rumen fermentation characteristics have been widely studied, but results are inconsistent between different studies. A quantitative meta-analysis was applied to 110 papers, 157 experiments, and 376 treatments dealing with yeast supplementation in ruminants. The objective was first to highlight the major quantitative effects of live yeast supplementation on intake, rumen fermentation, and milk production, and second, to identify major differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
268
8
22

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(319 citation statements)
references
References 15 publications
21
268
8
22
Order By: Relevance
“…Data on the effects of S. cerevisiae on microbiome composition are not available in the literature, and some evidence, summarized by Desnoyers et al (2009) and Robinson and Erasmus (2009), does not allow to postulate how yeast can affect the rumen bacterial microbiome. The results presented in Table 2 for the three experimental diets indicate a limited influence of dried yeast (DY group) on rumen bacteria, which is significant (P < 0.05) for the percentages of Bacillus (P < 0.05), for a non-assigned genus of Erysipelotrichaceae, and for a non-assigned genus of the phyla TM7 and Tenericutes, even if the metabolic meaning of these variations is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the effects of S. cerevisiae on microbiome composition are not available in the literature, and some evidence, summarized by Desnoyers et al (2009) and Robinson and Erasmus (2009), does not allow to postulate how yeast can affect the rumen bacterial microbiome. The results presented in Table 2 for the three experimental diets indicate a limited influence of dried yeast (DY group) on rumen bacteria, which is significant (P < 0.05) for the percentages of Bacillus (P < 0.05), for a non-assigned genus of Erysipelotrichaceae, and for a non-assigned genus of the phyla TM7 and Tenericutes, even if the metabolic meaning of these variations is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis (Desnoyers et al, 2009;Robinson and Erasmus, 2009) of published lactation experiments with S. cerevisiae supplementation has shown an increase in milk production of 0.9 kg milk/day or 1.2 g milk/kg BW, but many factors were claimed to interfere with the results (e.g. strain and level of supplementation, DMI, dietary NDF, % of dietary concentrates).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is a major concern to prevent or alleviate the occurrence of SARA in dairy herds. In the past decade, several dietary strategies proposed for use in preventing SARA, such as sodium bicarbonate buffer and monensin iono-phones as well as probiotics, have been found to stabilise ruminal pH and improve animal production (Mutsvangwa et al 2002;Paton et al 2006;Chaucheyras-Durand et al 2008;Desnoyers et al 2009;Packer et al 2011). However, none of these approaches has consistently maintained higher and stable ruminal pH.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast cultures of Saccharomyces cerevisiae have also been reported to stimulate lactate utilization by S. ruminantium and M. elsdenii , and could contribute to increase rumen pH (Chaucheyras-Durand et al, 2012). As previously reviewed (Desnoyers et al, 2009;De Ondarza et al, 2010), S. ruminantium supplementation to dairy cattle increases in milk production, but studies on beef cattle are scarce and controversial. Inconsistences in the response to malate and S. ruminantium supplementation may be explained by variations in the dose, growth rate and age of the animal, diet composition and farming conditions, among other factors (Yoon and Stern, 1995;Carro and Ungerfeld, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…These authors reviewed 14 experiments with dairy cattle and reported that fat-corrected milk production was increased on average by 3.5% (P<0.01) in dairy cows supplemented with S. cerevisiae, with significant improvements in feed efficiency (1.75 vs. 1.70 kg/kg for live yeast and control, respectively; P<0.01), milk fat yield (1.28 vs. 1.25 kg/d; P<0.01) and milk true protein yield (1.02 vs. 1.00 kg/d; P<0.001); without any effect on DMI. Desnoyers et al (2009) also performed a meta-analysis (involving 110 scientific papers and 157 experiments) on the effects of live S. cerevisiae cultures on ruminal parameters in dairy and growing cattle, sheep, goats and buffaloes. These authors concluded that yeast supplementation increased rumen pH (+0.03 on average) and ruminal VFA concentrations (+2.17 mM on average), tended to decrease lactic acid concentrations (-0.9 mM on average), increased DMI (+0.44 g/kg of BW) and milk yield (+1.2 g/kg of BW), and tended to increase milk fat content (+0.05%).…”
Section: Rumenmentioning
confidence: 99%